Unilateral Euroisation of Polish Foreign Exchange Law - Gorgol, Andrzej (The Opole Studies in Administration and Law, 2023)
The aim of the Article is to determine the extent and degree of the unilateral euroisation of Polish foreign exchange law. The research problem is analysed from the point of view of the current or previously applicable law. The unilateral euroisation of Polish foreign exchange law is already over 22 years old and is under the order of two successive foreign exchange laws of 1998 and 2002. This process has led to changes in both general and specific legal provisions. The author focused his agenda on demonstrating the accuracy of the idea that Polish foreign exchange law evolves in such a way that the degree of its euroisation increases. This is demonstrated, inter alia, by leaving residents and non-residents the choice between the euro and the Polish currency to apply either or one of these means to make payments and other foreign exchange transactions.